The Effect of Product Design, Promotion and Location on the Purchase Decision on the Green Java Housing, Kemang Bogor - Resti Rahmawati; Samsuri; Ismartaya (MultiTech Publisher, 2023)
Housing problems often occur in metropolitan areas or districts when the number of available houses is less than the total population, but people's purchasing power is relatively low due to slowing economic growth. Therefore, This research was done to determine the effects of consumer purchasing decisions on The Green Java Kemang Bogor housing. The main purpose of this review evaluate as well as pinpoint in what way product advertising, design, and location may all or some of the time have an impact on buying choices at The Green Java Kemang Bogor Housing. Contact was made with 58 respondents who had been chosen by purposive sampling and given questionnaires. The questionnaire has undergone validity, reliability, and the traditional assumption test. The test's findings are accurate and valid, and they may be used to data for regression. In this study, a quantitative approach and a descriptive and verification method were used as analytical techniques. The findings demonstrated that factors such as product design, promotion, and location had an impact on buying decisions either concurrently or in part.